2022
DOI: 10.1007/s11126-022-09971-w
|View full text |Cite
|
Sign up to set email alerts
|

An Update of Peer Support/Peer Provided Services Underlying Processes, Benefits, and Critical Ingredients

Abstract: The purpose of this article is to delineate the current state-of-the-knowledge of peer support following the framework employed in the 2004 article (Solomon, Psychiatr Rehabil J. 2004;27(4):392-401 1). A scoping literature was conducted and included articles from 1980 to present. Since 2004, major growth and advancements in peer support have occurred from the development of new specializations to training, certification, reimbursement mechanisms, competency standards and fidelity assessment. Peer support is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 66 publications
1
48
0
Order By: Relevance
“…Mutual aid refers to the reciprocal support and help between peers with similar experiences [46]. Mutual aid was mostly rooted in the reciprocity between people with the relevant lived experience of the concerned problems, without formal training or involvement of healthcare professionals [55]. The structural marginalization of MDWs from the health and social care system leaves MDWs with mutual aid as their only option [46,47].…”
Section: Mutual Aidsmentioning
confidence: 99%
“…Mutual aid refers to the reciprocal support and help between peers with similar experiences [46]. Mutual aid was mostly rooted in the reciprocity between people with the relevant lived experience of the concerned problems, without formal training or involvement of healthcare professionals [55]. The structural marginalization of MDWs from the health and social care system leaves MDWs with mutual aid as their only option [46,47].…”
Section: Mutual Aidsmentioning
confidence: 99%
“…Specifically, findings of the RCT conducted by Griffiths et al [20] suggested that engaging in a moderated depression internet support group may be clinically effective (ie, reducing depressive symptoms) in the long term, with potential short-term improvements for empowerment as presented in a companion paper of Crisp et al [20,21] reporting on the same trial. In addition to this quantitative evidence from a single trial for a depression PSI, descriptive systematic reviews (ie, a narrative synthesis for the efficacy of PSIs, not including a meta-analysis that systematically assesses the results of previously conducted studies) emphasize the potential of online health-related PSIs in general [22][23][24][25] and that of those specifically addressing depression [11,26].…”
Section: The Effectiveness Of Peer Supportmentioning
confidence: 99%
“…Several studies and systematic reviews reflect a practice of sexualised drug use among GBMSM and observe sexual risk taking, poor mental health and psychosocial outcomes among their participant samples; noting complex relationships between sexualised drug use and health outcomes [38][39][40][41][42]. Peer led service based responses addressing these mental health and substance use disparities often prioritise intervention modalities that can be tailored to individual experiences [43].…”
Section: Introductionmentioning
confidence: 99%